Enhanced photocatalytic degradation of methylene blue using a novel counter-rotating disc reactor - Ghasemi, Amir Hossein; Zoqi, Mohamad Javad; Zanganeh Ranjbar, Payam (Frontiers in Chemistry, 2024)
This research introduces an innovative photocatalytic reactor designed to address challenges in wastewater treatment, with a focus on enhancing dye degradation and reducing Chemical Oxygen Demand (COD). Uniquely, the reactor utilizes counter-rotational movements of discs to improve hydrodynamics and mass transfer, facilitating natural mixing and aeration. Additionally, the integration of a 3D-printed, interchangeable component system significantly enhances reactor efficacy. The experiments employ TiO2 nanoparticles, a mixture of 80% anatase and 20% rutile, thermally immobilized on glass discs. This study evaluates the effectiveness of various treatment variables in wastewater treatment using a comprehensive Central Composite Design (CCD), informed by a Response Surface Methodology (RSM) model. The RSM analysis reveals that the linear, quadratic, and interactive effects of the counter-rotational movements significantly influence the efficiency of dye and COD removal. The RSM model yields coefficients of determination (R2) values of 0.9758 and 0.9765 for the predictive models of dye and COD removal, respectively. Optimized parameters for dye removal include a pH of 6.05, disc rotation speed of 22.35 rpm, initial dye concentration of 3.15 × 10-5 M, residence time of 7.98 hours, and the number of nanoparticle layers set at 3.99, resulting in 96.63% dye removal and 65.81% COD removal under optimal conditions. Notably, the reactor demonstrates potential for efficient treatment within a near-neutral pH range, which could reduce costs and resource use by eliminating the need for pH adjustments. The implementation of discs rotating in opposite directions marks a significant advancement in the process of dye removal.